2020
DOI: 10.1186/s12974-020-01974-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient control of Japanese encephalitis virus in the central nervous system of infected pigs occurs in the absence of a pronounced inflammatory immune response

Abstract: Background Japanese encephalitis virus (JEV) is the leading cause of viral encephalitis in Asia. JEV infection of mice and humans can lead to an uncontrolled inflammatory response in the central nervous system (CNS), resulting in a detrimental outcome. Pigs act as important amplification and reservoir hosts, and JEV infection of pigs is mostly subclinical. Information on virus spread in the CNS and immune responses controlling JEV infection in the CNS of pigs, however remains scarce. Methods Nine-week-old pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 50 publications
4
27
1
Order By: Relevance
“…After having studied the local viral replication, cytokine mRNA expression, and evolution of immune cell frequency in the tonsils, we studied the induction of the peripheral adaptive immune response upon JEV infection. In our previous publication reporting on the same pigs from the first in vivo experiment, we already showed that first JEV specific antibodies could be detected between 5 and 7 days post infection onwards (Redant et al, 2020). These results were confirmed in the pigs from the second experiment.…”
Section: Humoral Immune Responsesupporting
confidence: 79%
See 2 more Smart Citations
“…After having studied the local viral replication, cytokine mRNA expression, and evolution of immune cell frequency in the tonsils, we studied the induction of the peripheral adaptive immune response upon JEV infection. In our previous publication reporting on the same pigs from the first in vivo experiment, we already showed that first JEV specific antibodies could be detected between 5 and 7 days post infection onwards (Redant et al, 2020). These results were confirmed in the pigs from the second experiment.…”
Section: Humoral Immune Responsesupporting
confidence: 79%
“…cDNA Synthesis and Preamplification cDNA synthesis was done as previously described (Verpoest et al, 2018;Redant et al, 2020). Following the manufacturer's instructions, extracted RNA was treated with Turbo DNase (Thermo Fisher) to eliminate genomic DNA.…”
Section: Jev Isolation and Titration In Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high degree of identity between encephalitic flaviviruses, antibody cross-protective immunity is observed. Brain damage and neuronal loss during JEV infections are associated with increased inflammation marked by increased levels of TNF-α, IL-1β, CCL5, CCL2 and NO [ 99 , 100 ]. JEV infection in humans and mice leads to cellular infiltration in the brain and spleen with major increases in neutrophil counts in the periphery and in the CSF.…”
Section: Participation Of Neutrophils and Neutrophil-associated Molecules In Flaviviral Diseasesmentioning
confidence: 99%
“…Controlled in vivo challenge models remain the gold standard for investigating the complexities of viral pathogenesis, and recent studies have provided valuable insights toward a better understanding of JEV infections in swine [24,25,27,[35][36][37]. However, host and virus factors associated with JEV pathogenesis remain poorly understood and advances in treatment and prevention in swine have been hindered by a lack of thorough understanding of the viral replication cycle and host-virus molecular interactions.…”
Section: Introductionmentioning
confidence: 99%